2012
DOI: 10.4172/1948-5956.1000174
|View full text |Cite
|
Sign up to set email alerts
|

Acacia Honey Modulates Cell Cycle Progression, Pro-inflammatory Cytokines and Calcium Ions Secretion in PC-3 Cell Lines

Abstract: Background: Prostate cancer is the most common malignancy in men and the second leading cause of cancer-related deaths. Honey has been proven to have a potentiality of being among the functional foods by both in vivo and in vitro studies. Aim:This study was primarily designed to provide evidence on the apoptotic role of acacia honey on PC-3 cell line. Methods:MTT and mitotic index assay were used to determine the anti-proliferative effects. Cell cycle analysis was conducted on flow cytometer using propidium io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Honey treatment of bladder cancer cell lines was shown to cause a considerable arrest of cell cycle in the sub-G 1 phase [68]. Recently, Aliyu and colleagues also showed that the cytotoxic effect of honey against non-small cell lung cancer cell (NCI-H460) was mediated via arrest of cell cycle at G 0 /G 1 phase [79]. Available data reveal that the ability of honey to arrest cell cycle is due to the various flavonoids and phenolic compounds in honey.…”
Section: Mechanisms Of the Antiproliferative Antimetastatic And Amentioning
confidence: 99%
“…Honey treatment of bladder cancer cell lines was shown to cause a considerable arrest of cell cycle in the sub-G 1 phase [68]. Recently, Aliyu and colleagues also showed that the cytotoxic effect of honey against non-small cell lung cancer cell (NCI-H460) was mediated via arrest of cell cycle at G 0 /G 1 phase [79]. Available data reveal that the ability of honey to arrest cell cycle is due to the various flavonoids and phenolic compounds in honey.…”
Section: Mechanisms Of the Antiproliferative Antimetastatic And Amentioning
confidence: 99%
“…Cytokine activity is influenced by the microenvironment in which they are produced and as such may have pro-(Th1) or anti-inflammatory (Th2) actions [12]. Tumor necrosis factor (TNF-α), an inflammatory cytokine that is highly expressed in breast and cervical carcinomas play an important role in the regulation of both induction and protection in breast and cervical cancer [13,14], and apoptosis [15].…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive compounds such as (+)-catechin, (−)-epicatechin, (−)-epicatechin-3- O -gallate, epigallocatechin-3- O -gallate, quercetin, and (+)-cyanidanol have been isolated from different Acacia species 15 . Compounds identified from Acacia species are known to modulate various signaling pathways in breast and prostate cancer 18 19 . However, these studies have generally utilized the total extracts from various catechin sources reflecting effects of combined activities of several compounds rather than of a single compound.…”
mentioning
confidence: 99%